Eletrocoagulação seguida de ultrafiltração para pós-tratamento de esgoto para reuso doméstico não potável - Brião, Edesnei Brabosa (2015)
The conservation of water resources is an essential demand for the sustainability of society. The reuse of effluents is essential to balance the water balance between water abstraction and effluent disposal. In general, the effluent treated by Sewage Treatment Plants (ETS) does not have sufficient quality for reuse, as these ETEs are usually designed only to comply with the legislation. The water produced by TEEs also contains pollutants that need to be removed to achieve sufficient quality for reuse, such as suspended and colloidal solids that escape through the gravity-based water / slurry separation system (decanters). Therefore, it is necessary to use post-treatments to improve the quality of this effluent before reuse. This work aims to apply electrocoagulation (EC) treatment techniques and membrane separation processes (PSM) to obtain water with the quality required for reuse. While the electrocoagulation allows to obtain flakes with operational ease and good efficiency in the removal of pollutants, the ultrafiltration has high selectivity in the separation microflocos, colloids and suspended matter. Therefore, the combination of the two techniques can produce water with excellent quality, reducing the risks in its reuse. The operating conditions of the EC process were tested in the first step, aiming to determine the current density and the constructive material of the electrodes (steel or aluminum). After determination of the best operating conditions of the EC process, a continuous EC reactor was tested to produce water to feed a subfiltered microfiltration and ultrafiltration system. The results with aluminum electrodes and current density of 50 W / m² had better performance than steel electrodes and current density of 75 W / m². Residual times of 40 minutes were sufficient to improve the quality of the effluent produced, with the removal efficiencies of the Chemical Oxygen Demand of 50% suspended solids in 80%. In the combination of EC and ultrafiltration these efficiencies were improved to 90% and 100%, respectively. The water produced reached Class 2 reuse quality because the effluent from the ETE had a COD in the order of 250 mg / L or more and the efficiencies were not enough to obtain quality for Class 1 reuse. is a promising alternative for the production of reuse water.